PENERAPAN IDEF1X UNTUK ARSITEKTUR DATABASE PADA ENTERPRISE ARCHITECTURE PLANNING (EAP) - Agus Nursikuwagus (Jurnal Computech & Bisnis (e-Journal), 2015)
This research is to assist the implementation of an architectural model of a database by using IDEF1X. Utilization IDEF1X model is very easy to apply. The use of diagrams consisting of a square shape and the arrow represents the shape of the data as well as the connection between the data. It is applied to describe the architecture of the database that is part of the Enterprise arhitecture stages Planning (EAP) from Stephen Spewak. The idea of IDEF1X is to minimize the complicated form of the description of database architecture. Where this model is the definition of database architecture models with reference to business entities in the business functions in the Enterprise. Keywords: IDEF1X, Database Architecture, Enterprise Architecture Planning   Abstrak Penelitian ini untuk membantu penerapan suatu model arsitektur database dengan menggunakan IDEF1X. Pemanfaatan model IDEF1X sangat mudah untuk diterapkan. Penggunaan diagram yang terdiri atas bentuk persegi dan panah merepresentasikan bentuk dari data serta koneksi antar data tersebut. Hal ini diterapkan untuk menggambarkan arsitektur database yang merupakan bagian tahapan dari Enterprise Arhitecture Planning (EAP) dari Stephen Spewak. Ide dari IDEF1X adalah meminimalkan bentuk yang rumit dari penggambaran suatu arsitektur database. Dimana model ini merupakan model pendefinisian dari arsitektur database dengan mengacu pada entitas bisnis pada fungsi bisnis di Enterprise. Kata kunci : IDEF1X, Arsitektur Database, Enterprise Architecture Planning